Ultrasound-triggered drug release and cytotoxicity of microbubbles with diverse drug attributes - Chi-Fen Chuang; Chia-Wei Lin; Chih-Kuang Yeh (Ultrasonics Sonochemistry)
Ultrasound (US)-triggered cavitation of drug-loaded microbubbles (MBs) represents a promising approach for targeted drug delivery, with substantial benefits attainable through precise control over drug release dosage and form. This study investigates Camptothecin-loaded MBs (CPT-MBs) and Doxorubicin-loaded MBs (DOX-MBs), focusing on how properties such as hydrophilicity, hydrophobicity, and charged functional groups affect their interaction with the lipid surfaces of MBs, thereby influencing the fundamental characteristics and acoustic properties of the drug-loaded MBs. In comparison to DOX-MBs, CPT-MBs showed larger MB size (2.2 ± 0.3 and 1.4 ± 0.1 μm, respectively), a 2-fold increase in drug loading, and an 18 % reduction in leakage after 2 h at 37℃. Under 1 MHz US with a 100 ms pulse repetition interval (PRI), 1000 cycles, 5-minute duration, and 550 kPa acoustic pressure, CPT-MBs undergo inertial cavitation, while DOX-MBs undergo stable cavitation. Drug particles released from these MBs under US-induced cavitation were analyzed using dynamic light scattering, NanoSight, cryo-electron microscopy, and density gradient ultracentrifugation. Results showed that CPT-MBs mainly release free CPT, while DOX-MBs release multilayered DOX-lipid aggregates. The cytotoxicity to C6 cells induced by US-triggered cavitation of these two types of MBs also differed. DOX-lipid aggregates delayed initial uptake, leading to less pronounced short-term (2 h) effects compared to the rapid release of free CPT from CPT-MBs. These findings underscore the need to optimize drug delivery strategies by fine-tuning MB composition and US parameters to control drug release kinetics and achieve the best tumoricidal outcomes.